Edu science: interactive science learning / Siti Nur Fhaiqah Syed Jamaludin - Syed Jamaludin, Siti Nur Fhaiqah (Faculty of Art and Design, 2020)
Edu Science is a mobile application that thrives and enables the school students to use an interactive tool, purposely for the seamless connect and interact outside the classroom and leads to a contribution to education sector in Malaysia.